EXAMINING PORT CITY DEVELOPMENT AS A STRATEGY TO ATTRACT CRUISE VISITORS - SELVADURAY, MAHENDRRAN; BANDARA, YAPA MAHINDA; YUNUS, NORHASLINDA (Journal of Maritime Logistics, 2023)
The expansion of urban development and commercial centers within the geographical boundaries of ports and cities has significantly contributed to the growth of national income. However, maritime-based countries face the challenge of staying competitive in the dynamic port-city landscape. To address these issues, this paper employs a bibliometric approach to review existing literature on port-cities, identifies challenges faced by port-cities as cruise visitor attractions, and proposes a new framework for their sustainable future in the maritime cruise industry. By analysing 73 journal articles through VoS Viewer and employing content analysis with NVivo 12 software, the paper presents a problem-solving guideline framework that can aid nations in tackling major challenges related to port-city development and cruise tourism.